Neuromyotonia in a horse - Zakia, Luiza Stachewski [UNESP]; Palumbo, Mariana Isa Pocci; Teixeira, Raffaella Bertoni Cavalcanti; Resende, Luiz Antônio Lima [UNESP]; Soares, Mauro Pereira; de Oliveira-Filho, José Paes [UNESP]; Amorim, Rogério Martins [UNESP]; Borges, Alexandre Secorun [UNESP] (Oxford University Press (OUP), 2019)
This article describes the clinical and electromyographic findings of neuromyotonia in a 19-month-old male crossbred Quarter Horse that presented with stiffness and muscle asymmetry in the hind limbs as well as sacrococcygeal, paravertebral, and gluteal myokymia. An electromyographic study showed spontaneous continuous muscle fiber activity with high-frequency discharges, fibrillations, positive sharp waves, fasciculation potentials, and complex repetitive discharges. Histological examination of the gluteal muscle showed a mixed neurogenic and myopathic pattern. The findings are consistent with neuromyotonia.
Keywords: electromyography; equine; myokymia; myopathy; stiffness